Desenvolvimento e validação de método bioanalítico aplicado em estudo de farmacocinética pré-clínica e ensaio preliminar de segurança de novo derivado de tiazolidinodiona com atividade antiinflamatória - LYSO-07 - Padilha, Elias Carvalho [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Thiazolidinediones (TZDs) are agonists of PPAR-γ (peroxisome proliferator-activated receptor) receptor whose activation modulates the expression of about 100 genes, which gives this class of drugs several actions in the body as the control of blood glucose, cholesterol and anti - inflammatory activity. Among the TZDs that were released on the market, only pioglitazone remains available once their predecessors - rosiglitazone and troglitazone - showed high toxicity. Considering the vast therapeutic potential of TZDs, researchers from the Laboratory of Drug Synthesis and Planning from the Federal University of Pernambuco synthesized the LYSO-07, a thiazolidine- 2,4-dione derivate whose biological activity assays demonstrated that the new TZD has a promising anti-inflammatory effect. In the development of new drugs the early assessment of their pharmacokinetic profile and toxicity is unavoidable in order to obtain relevant information of the risks of the molecule and contribute to the advancement of the studies of the new molecule. The present study assessed the physicochemical properties and the single dose pharmacokinetic profile of the new molecule in rats administered intravenously and by gavage. Further, some biochemical parameters were measured to assess the effects of the exposure of LYSO-07 ((5-(5-bromo-1H-indol-3-methylene)-3-(4-chlorobenzyl)-thiazolidine-2,4-dione) to rats in multiple doses for 28 days administered by gavage. The LYSO-07 showed instability in an aqueous environment at pH 7.4 and 1.2 and log P above 6.5. Pharmacokinetic parameters determined after IV administration were: elimination half-life (t1/2) of 2.3 hours, clearance (Cl) 33.18 mL/min/kg and volume of distribution (Vd) of 6,648.71 mL/kg. The LYSO 07 could not be detected in the plasma of animals given the compound by gavage (LOQ=78.125 ng/mL). The 28 days of exposure of animals at a dose of ...

As tiazolidinodionas (TZDs) são fármacos agonistas do receptor PPAR-γ (peroxisome proliferator activated receptor) cuja ativação leva a modulação de cerca de 100 genes, o que confere a esta classe de fármacos diversas ações no organismo como o controle de glicemia, do colesterol e atividade antiinflamatória. Entre as TZDs que foram lançadas no mercado apenas a pioglitazona permanece disponível uma vez que suas antecessoras rosiglitazona e troglitazona - apresentaram alta toxicidade. Considerando o vasto potencial terapêutico das TZDs, pesquisadores do Laboratório de Planejamento e Síntese de Fármacos da Universidade Federal de Pernambuco sintetizaram a LYSO-07 ((5-(5-bromo-1H-indol-3-metieleno)-3-(4-cloro-benzil)tiazolidina-2,4-diona), um derivado tiazolidino-2,4-diona cujos ensaios de atividade biológica demonstraram que a nova TZD possui atividade antiinflamatória promissora. No desenvolvimento de novos fármacos é impreterível a avaliação precoce do seu perfil farmacocinético e de sua toxicidade com o intuito de obter informações relevantes à avaliação de risco e ao avanço dos estudos com a nova molécula. No presente trabalho foram avaliados aspectos físico-químicos e o perfil farmacocinético em dose única da nova molécula administrada em ratos Wistar por via intravenosa e por gavagem. Ainda, foram determinados alguns parâmetros bioquímicos para avaliar os efeitos da exposição de ratos Wistar a doses múltiplas de LYSO-07 por 28 dias administrado por gavagem. A LYSO-07 apresentou instabilidade em ambiente aquoso em pH 1,2 e 7,4 e logP acima de 6,5. Os parâmetros farmacocinéticos determinados após administração via intravenosa foram: meia vida de eliminação (t1/2) de 2,3 horas; clearance (Cl) de 33,18 mL/min/Kg e volume de distribuição (Vd) de 6.648,71 mL/kg. A LYSO-07 não foi detectada no plasma dos animais que receberam...
Keywords: Farmacocinética; Ratos Wistar; Bioquímica; Físico-química; Cromatografia líquida de alta eficiência; Espectrometria de massa; Toxicologia; High performance liquid chromatography